Movimentos sociais : na trama subliminar do ocultamento dos conflitos de classe - Santos, Marleide Maria (2008)
The present study is centered in the conception of Social Movements while expression of the content of the division and of the conflicting relations among the social class. In that sense, it is understood the construction of the notion of Social Movement and its unfoldings, as part of a wide project, that is mined, in the ideological plan, the social conflicts, through the politics of the collaboration among the classes and of the consequent remeaning of the conflicts. The analysis perspective that permeated the debates, around the Social Movement category, in the years 1980/1990, pointed the emergency of "New Social" Movements (NMS) related to the supposed loss of the centrality of the work and of the crisis of the class struggle, under the paradigm of the culture. In the opposite direction of that affirmative and its presuppositions, our analysis was based in the dialectical method that allows verifying, starting from the category totality, that the social conflicts exist equal and step in its contradictions, independent of what is put as cultural identity. It is defended in this thesis that the memory of the peasants struggles in Brazil, stippled of manifestations and historical experiences, are evidences in the several ways of reactions to the exploration logic, below the syntony of interest of the hegemonic class, in the power, articulated with the State, fact so well evidenced in our geographical historical Brazilian formation, in the Northeastern semi-arid. In this inclination it was fundamental to understand the reason why the semi-arid has been constituted as appropriation territory and convergence of interests of the capital, metamorphosed in the rhetorical speech of the geographical naturalization, but that, concretely, it is configured in government programs that guarantee the conformation of the social and territorial inequality of the labour. In this path the field research accomplished in the Territory of the Alto Sertão Sergipano proved as the proposal of a new rural development, now backed in the local development, with focus in the territory, it is part of a strategy with many faces, formulated by the neoliberal State and for its cooperators and international allies, to contain insurrection of the rural workers without their own land. Engendered in the salience of the development politics for relief of the rural poverty, the territorial development is organized to neutralize the tactics of direct actions of the popular movements, such as the Movimento dos Trabalhadores Rurais Sem Terra - MST; Movimento dos Pequenos Agricultores - MPA, and Movimento dos Atingidos por Barragens - MAB. The territory is presented as planning instrument, in which, illusionality, are found the solutions for the problems of the local population. The Social Movements have been facing the challenge of being part of that architecture of legitimation of the ideological character of the dominant class that is dressed on the speech of the administration of collective participation. Such perspective aims to neutralize the conflicts, to guarantee the conciliation and, to justify the conflicts as actions of criminalization of the Social Movements. As resistance the Social Movements try to enlarge their scales of performances, to narrow and to intensify the alliances, in the sense to assure and to reaffirm their beginnings and their struggle flag. To Geography, the task is to think, to contemplate, to watch and to reveal this reality, permeated of contradictions, in the way as the capital produces and reproduces spaces self-territorializing, and to present alternatives of overcoming possibilities to the warranty of the alternative territories of the peasant population.